Fermat’s Principle – Concave Mirror

Fermat’s - Fermats Principle Concave Mirror y a z = f(y b z-f z0 z0 represents an arbitrary reference plane a = z0 z b2 = y2 f z

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Fermat’s Principle – Concave Mirror z 0 represents an arbitrary reference plane. () 0 22 az z by f z =− + =++ With the sign conventions for “b”; b is negative as shown: 2 2 f z =− + + Determine the two optical path lengths. Remember that the index changes sign after a reflection: (n = 1 in air) ( ) 0 1 a b OPL na z z OPL n b y f z y f z == + ⎛⎞ =− − + + = ⎜⎟ ⎝⎠ Fermat’s principle requires that the total OPL be constant: ab OPL OPL Constant += z a b y -f z 0 z = f(y)
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This sum can be evaluated exactly along the optical axis (z = 0 at y = 0): 0 ab OPL OPL z f += + Equate this value with the total OPL for an arbitrary y: () 2 2 00 22 2 2 2 2 4 4 zf zz y f z fz y ff z z y z z yf z y z f −+=
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 12/17/2010 for the course OPTI 502 taught by Professor Greivenkamp during the Fall '08 term at University of Arizona- Tucson.

Page1 / 2

Fermat’s - Fermats Principle Concave Mirror y a z = f(y b z-f z0 z0 represents an arbitrary reference plane a = z0 z b2 = y2 f z

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online